Changes in cerebral blood flow during olfactory stimulation in patients with multiple chemical sensitivity: a multi-channel near-infrared spectroscopic study. - Kenichi Azuma (PLoS ONE, 2013)
Multiple chemical sensitivity (MCS) is characterized by somatic distress upon exposure to odors. Patients with MCS process odors differently from controls. This odor-processing may be associated with activation in the prefrontal area connecting to the anterior cingulate cortex, which has been suggested as an area of odorant-related activation in MCS patients. In this study, activation was defined as a significant increase in regional cerebral blood flow (rCBF) because of odorant stimulation. Using the well-designed card-type olfactory test kit, changes in rCBF in the prefrontal cortex (PFC) were investigated after olfactory stimulation with several different odorants. Near-infrared spectroscopic (NIRS) imaging was performed in 12 MCS patients and 11 controls. The olfactory stimulation test was continuously repeated 10 times. The study also included subjective assessment of physical and psychological status and the perception of irritating and hedonic odors. Significant changes in rCBF were observed in the PFC of MCS patients on both the right and left sides, as distinct from the center of the PFC, compared with controls. MCS patients adequately distinguished the non-odorant in 10 odor repetitions during the early stage of the olfactory stimulation test, but not in the late stage. In comparison to controls, autonomic perception and negative affectivity were poorer in MCS patients. These results suggest that prefrontal information processing associated with odor-processing neuronal circuits and memory and cognition processes from past experience of chemical exposure play significant roles in the pathology of this disorder.